Strict volume control can improve structure and function of common carotid artery in hemodialysis patients - Gunal, Ali Ihsan; Karaca, Ilgin; Ozalp, Goksel; Ozturk, Abdullah; Dogukan, Ayhan; Celiker, Huseyin (Wichtig Editore, 2006)
Background. Damage in large arteries, characterized by increased intima-media thickness and decreased compliance, is frequent in hemodialysis patients and increases cardiovascular morbidity and mortality. Since volume overload and hypertension may accelerate atherosclerosis in patients with chronic renal failure, the aim of this 1-year study was to assess whether strict volume control would improve structural and functional abnormalities of the common carotid artery in hypertensive hemodialysis patients. Methods: We conducted a prospective study (n=16) for 1 year to investigate the effect of strict volume control on intima-media thickness and compliance of the common carotid artery. Intima-media thickness was assessed by echocardiography. Results: All patients were normotensive without antihypertensive drugs at the end of follow-up. During the follow-up period, continuous efforts were made to further reduce blood pressure if necessary. This resulted in a gradual further improvement in several of the measured parameters. The cardiac index did not significantly change throughout the study. The most important finding was a marked decrease in the intima-media thickness of the common carotid artery (p < 0.000). This decrease in intima-media thickness was accompanied by significant amelioration in the arterial compliance of the common carotid artery (p < 0.000) and consequently of the systemic vascular resistance index (p < 0.004). Conclusion: In conclusion, a strict volume control strategy effectively improves vascular abnormalities. Moreover, this study demonstrates the possible role of vascular stiffening in blood pressure regulation in patients with chronic renal failure.
Keywords: hemodialysis; hypertension; strict volume control; interdialytic weight gain; intima-media thickness; arterial compliance